Būṭā Siṅgha - Dhīmāna, Harabam̆sa Siṅgha (Pabalīkes̱ana Biūro Pañjābī Yūnīvarasiṭī, 2010)
On the life and works of Boota Singh, b. 1917, Panjabi author
Includes bibliographical references (p. [155]). - Panjabi in Gurmukhi-Schr
Keywords: Boota Singh 1917-; Authors; Panjabi